Freeze-drying kinetics and diffusion modeling of hawthorn - Hagig, Khaled Ali; Acar, Bahadir; Dagdeviren, Abdullah; Taskesen, Edip; Ozkaymak, Mehmet (Yildiz Technical Univ, 2023)
This study tests freeze-drying (FD) technology (Scanvac Coolsafe model, Labogene brand) to preserve hawthorn fruit. First, 100g hawthorn slices were frozen and then freeze-dried. Kinetic models were applied, and hawthorn's moisture ratio and weight loss were noted after every two hours during the 14-hour freeze-drying process. Matlab program is used to perform a total of eight kinetic drying models. Results show that the root mean square error was 0.011063, the highest determination coefficient was 0.9987, the least chi-square was 1.959x10(-4), and the effective diffusivity was 2.33742x10(-1)0m(2)/s. The diffusion approach is the best among the eight models.
Keywords: Drying kinetics; Freeze-drying; Kinetic drying model; Diffusion approach model; Drying hawthorn